Apakah Ukuran Perusahaan, Kompleksitas Perusahaan, Leverage, Profabilitas dan Komite Audit Mempengaruhi Biaya Audit? - Rifaldi, Muhamad Rifay (Owner : Riset dan Jurnal Akuntansi, 2024)
Audit Fee is the amount of imbalance that will be accepted by public accountants by adjusting the assignment, complexity of services and level of expertise related to providing financial report audit services. Rules regarding Audit Fees were made by the Indonesian Institute of Public Accountants (IAPI) in Management Regulation Number 2 of 2016 concerning "Determining Fees for Financial Report Audit Services". In reality, disclosing the amount of Audit Fees in some Companies is done implicitly, which means that Audit Fees are presented together with professional services in the Company's profit and loss report. This research aims to determine the influence of company size, company complexity, leverage, profitability and audit committee on audit fees in mining sector companies listed on the Indonesia Stock Exchange for the 2022-2023 period. The sample used in this research was 126 samples using purposive sampling. The data in this study were analyzed using descriptive analysis and linear regression. The analytical method used is linear regression using Eviews software version 12. The results of the research show that Company Size partially has a significant positive effect on audit fees, Company Complexity partially has a significant negative effect on audit fees, while Leverage and Profitability partially have no significant negative effect on audit fees and the Audit Committee partially do not have a significant positive effect on audit fees.. Keywords: Audit Fee, Company Size, Company Complexity, Leverage, Profitability, Audit Committe